A Topology‐Defined Polyester Elastomer from CO2 and 1, 3‐Butadiene: A One‐Pot‐One‐Step "Scrambling Polymerizations" Strategy. Issue 46 (17th October 2022) - Chen, Kaihao; Zhu, Zhiqi; Bai, Tianwen; Mei, Yixuan; Shen, Tianlun; Ling, Jun; Ni, Xufeng
Abstract: It is significant and challenging to use CO2 to produce polymeric materials, especially with olefins. Here, a novel strategy named "scrambling polymerizations" is designed and performed for the copolymerization of a CO2 ‐and‐1, 3‐butadiene‐derived valerolactone, 3‐ethylidene‐6‐vinyltetrahydro‐2H‐pyran‐2‐one (EVL), with ϵ‐caprolactone (CL) to prepare polyesters. Anionic ring‐opening polymerization of CL and conjugated addition oligomerization of EVL take place individually to form PCL and EVL oligomers, respectively. Then EVL oligomers insert into PCL by transesterification resulting in polyester P(CL‐co‐EVL) with a tunable topology and composition. The non‐cytotoxic and degradable polyester network with elongation at break of >600 % can be used as an elastomer. We propose a method to provide polyester elastomers from CO2 and olefins for the first time, and expand the potential of transformation from sustainable feedstocks to polymeric materials. Abstract : A novel strategy named "scrambling polymerizations" is realized to produce polyester with tunable topologies by one‐pot‐one‐step ring‐opening copolymerization of a substituted δ‐lactone derived from CO2 and 1, 3‐butadiene with ϵ‐caprolactone mediated by sodium phenolate. The obtained transparent, non‐cytotoxic and degradable network presents great resilience and excellent elastic recovery properties for application as a polyester elastomer.